Clinical Overview of Progressive Fibrotic Interstitial Lung Disease - Amy Hajari Case (Frontiers in Medicine, 2022)
Interstitial lung diseases (ILD) on the whole have variable prognoses, but there are those which manifest with fibrosis and are characterized by disease progression. Chief among these is idiopathic pulmonary fibrosis, but other ILDs, including autoimmune ILD and chronic hypersensitivity pneumonitis, may have a progressive fibrotic phenotype also. A usual interstitial pneumonia pattern of lung involvement is a prominent risk factor for such a course, suggesting shared fibrotic pathways that may be targeted by antifibrotic therapies. This brief review describes ILDs that are most commonly fibrotic, shared risk factors for development of PF-ILD, and evidence for antifibrotic use in their management.